Spectrophotometric Determination of Carbamazepine Via Oxidative Coupling Reaction with 2,4-dinitrophenyl hydrazine - R. Fadhel, Sahar; I. Abdulla, Najwa; D. Sulaiman, Intidhar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
An accurate and sensitive spectrophotometric method has been developed for the determination of carbamazepine (CRN.) in pure and dosage forms. The method is based on the oxidation of 2,4-dinitrophenylhydrazine (2,4-DNPHz) by potassium periodate than coupling with carbamazepine (CRN.) in alkaline medium to form a stable yellowish brown colored water-soluble dye with a maximum absorption at 485 nm. The variables that affect the completion of reaction have been carefully optimized. Beer’s law is obeyed over the concentration range of (4-50 μg.mL-1) with molar absorptivity of (6.7335×103 L.mol-1.cm1). The limit of detection was (0.1052 μg.mL-1) and Sandell’s sensitivity value was 0.0350 μg.cm-2.The proposed method has been applied successfully to the determination of carbamazepine in pharmaceutical preparation.